1999
DOI: 10.1080/14756369909030337
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study on the Interaction Between Tazobactam (A Penicillanic Acid Sulphone Derivative) and Active-Site Serine B-Lactamases

Abstract: The interaction between tazobactam and several chromosome- and plasmid-encoded (TEM, SHV, PSE types) class A and C beta-lactamases was studied by spectrophotometry. Tazobactam behaved as a competitive inhibitor or inactivator able to restore in several cases the efficiency of piperacillin as a partner beta-lactam. A detailed kinetic analysis permitted measurement of the acylation efficiency for some cephalosporinases and broad-spectrum beta-lactamases; the presence of a turn-over of acyl-enzyme complex was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Therefore, a %fTϾMIC of 30% (of an 8-h dosing interval) for an MIC of 4 g/ml (the Clinical and Laboratory Standards Institute susceptibility breakpoint for P. aeruginosa [14]) can be assumed to be a suitable PK/PD target for ceftolozane, based on existing regulatory PK/PD guidance for the development of antibacterial treatments for potentially life-threatening infections (15). Tazobactam is a competitive, essentially irreversible inhibitor of specific serine ␤-lactamases, including common ESBLs (16)(17)(18)(19). Since tazobactam does not have intrinsic antibacterial activity, an MIC cannot be determined.…”
mentioning
confidence: 99%
“…Therefore, a %fTϾMIC of 30% (of an 8-h dosing interval) for an MIC of 4 g/ml (the Clinical and Laboratory Standards Institute susceptibility breakpoint for P. aeruginosa [14]) can be assumed to be a suitable PK/PD target for ceftolozane, based on existing regulatory PK/PD guidance for the development of antibacterial treatments for potentially life-threatening infections (15). Tazobactam is a competitive, essentially irreversible inhibitor of specific serine ␤-lactamases, including common ESBLs (16)(17)(18)(19). Since tazobactam does not have intrinsic antibacterial activity, an MIC cannot be determined.…”
mentioning
confidence: 99%
“…Kinetic study showed that tazobactam is an efficient suicide inhibitor of β-lactamase produced of P. aeruginosa (Livermore et al, 1992;Perilli et al, 1999). The principal β-lactam resistance mechanism in P. aeruginosa in Italy seems principally due to combination of β-lactamase production and impermeability (Bonfiglio et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that β-lactamases function cooperatively with outer membrane impermeability to protect the Gram-negative cells from the antibacterial actions of β-lactam drugs (Livermore, 1988;Nikaido, 1989). Tazobactam is an excellent suicide β-lactamase-inhibitor (Livermore et al, 1992;Perilli et al, 1999). Piperacillin in association to tazobactam showed a very good activity against P. aeruginosa resistant strains isolated in intensive care units (Bonfiglio et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant with immense interests in the novel inhibitor discovery are the demands for efficient approaches for screening and characterizing a vast array of potential candidates that comes from nature or is generated from structure‐guided in‐parallel synthesis. Conventional approaches for identifying the potential drug candidates are microbial susceptibility testing and β‐lactamase inhibition assay . These methods determine the minimal inhibitory concentration (MIC) and inhibition constants (IC 50 or K i ) of the candidates respectively, thus providing indices for the drug potency.…”
Section: Introductionmentioning
confidence: 99%